2012
DOI: 10.1016/j.physa.2011.09.018
|View full text |Cite
|
Sign up to set email alerts
|

On Grover’s search algorithm from a quantum information geometry viewpoint

Abstract: We present an information geometric characterization of Grover's quantum search algorithm. First, we quantify the notion of quantum distinguishability between parametric density operators by means of the Wigner-Yanase quantum information metric. We then show that the quantum searching problem can be recast in an information geometric framework where Grover's dynamics is characterized by a geodesic on the manifold of the parametric density operators of pure quantum states constructed from the continuous approxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…In [4], the role of entanglement in quantum search was investigated in terms of the Fubini-Study metric. In [5,6], quantifying the notion of quantum distinguishability between parametric density operators by means of the Wigner-Yanase quantum information metric, it was shown that the quantum search problem can be recast in an information geometric framework wherein Grover's dynamics is characterized by a geodesic on the manifold of parametric density operators of pure quantum states constructed from the continuous approximation of the parametric quantum output state in Grover's algorithm. Finally, in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In [4], the role of entanglement in quantum search was investigated in terms of the Fubini-Study metric. In [5,6], quantifying the notion of quantum distinguishability between parametric density operators by means of the Wigner-Yanase quantum information metric, it was shown that the quantum search problem can be recast in an information geometric framework wherein Grover's dynamics is characterized by a geodesic on the manifold of parametric density operators of pure quantum states constructed from the continuous approximation of the parametric quantum output state in Grover's algorithm. Finally, in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The N-dimensional probability distribution vectorp (p 0 (θ ) , p 1 (θ ) ,..., p N 1 (θ )) with p k (θ ) defined in (14) can be regarded as a path characterizing Grover's algorithm on a suitable probability space. In what follows, we show that such a path is indeed a geodesic path for which the quantum Fisher information action functional achieves an extremal value.…”
Section: Grover's Search Algorithmmentioning
confidence: 99%
“…Our analysis explicitly recognizes that the Fubini-Study metric is a quantum version of the Fisher metric [11]. Substituting (18) into (17) and using (13) together with the normalization condition on the probabilities in (14), after some straightforward algebra it turns out that the infinitesimal Wigner-Yanase line element reads,…”
Section: Grover's Algorithm and Quantum Information Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…For recent discussions on the transition from the digital to analog quantum computational setting for Grover's algorithm, we refer to Ref. [4][5][6]. Ideally, one seeks to achieve unit success probability (that is, unit fidelity) in the shortest possible time in a quantum search problem.…”
Section: Introductionmentioning
confidence: 99%